The effect of ECD program on the caregiver's parenting knowledge, attitudes, and practices: based on a cluster-randomized controlled trial in economically vulnerable areas of China - Ying Li; Shanshan Li; Lei Tang; Yu Bai (BMC, 2022)
Abstract Background The first three years of life are the critical and sensitive periods for the formation of individual abilities. However, existing data indicates that early childhood development (ECD) in economically vulnerable areas of China is lagging, which is closely related to the lack of parenting knowledge and poor parenting practices. Methods We conducted a non-masked cluster-randomized controlled trial in a former nationally designated poverty county of China. All 6-36-month-old children and their caregivers living in 18 communities/clusters (10 towns and 8 districts of the county seat) were enrolled in a 9-month parenting training program. In the treatment-group communities, ECD centers were installed where community workers provided parenting training sessions. If caregivers were unable to visit the center, home-based parenting training was offered. No intervention was provided to the control group. Furthermore, we assigned half of the treatment group to receive monthly developmental feedback in addition to the parenting training. Based on the baseline and follow-up data, we investigated the treatment effects on parenting knowledge, attitudes, and practices through Intention-to-Treat (ITT) and Treatment-on-the-Treated (TOT) analyses. Results We found no effects on the parenting knowledge and attitudes of the caregivers but significant effects on the parenting practices. The effects were heterogeneous among families with different characteristics. Specifically, on average, the program had the largest effect on internally oriented caregivers, mothers with higher education, and mothers who are primary caregivers. We want to emphasize that, although the ITT effect on parenting practices (the average treatment effect) were stronger for mothers with higher education, the TOT effect on parenting practices (the local average treatment effect, LATE) were stronger for mothers with less education. That is, even though on average the program helped mothers with higher education, but among complier families, the program benefited mothers with less education. Conclusion The findings indicate that, at least in the short run, the program can directly change caregivers' parenting practices without changing their knowledge and attitudes. Future studies are needed to investigate whether parenting knowledge and attitudes can change in the long run.